2020
DOI: 10.1186/s13018-020-02071-0
|View full text |Cite
|
Sign up to set email alerts
|

Does the correction angle affect hidden blood loss in HTO?

Abstract: Background High tibial osteotomy (HTO) has a history of nearly 60 years and has been widely used in clinical practice. Biplanar open wedge high tibial osteotomy (BOWHTO), which evolved from HTO, is an important therapy for the knee osteoarthritis. In our previous research, we found that the decrease of hemoglobin levels after high tibial osteotomy ranges from between 17 to 41 g/L, but this is highly inconsistent with the intraoperative bleeding and postoperative drainage observed in clinical practice. The purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…When performing osteotomy, intravenous tranexamic acid and or topical tranexamic acid is recommended in order to reduce post-operative bleeding and swelling When performing osteotomy there are concerns over bleeding, with subsequent pain, swelling and thus reduced mobility. It has been shown that there is a significant hidden blood loss following OWHTO, proportionate to the size of the correction [40], which could be compounded by chemical thromboprophylaxis. Intravenous tranexamic acid has been shown to reduce blood loss in both tibial [41,42] and femoral osteotomy [43], with reduced length of stay for inpatient surgery.…”
Section: When Planning Osteotomy Patella Height Should Be Taken Into ...mentioning
confidence: 99%
“…When performing osteotomy, intravenous tranexamic acid and or topical tranexamic acid is recommended in order to reduce post-operative bleeding and swelling When performing osteotomy there are concerns over bleeding, with subsequent pain, swelling and thus reduced mobility. It has been shown that there is a significant hidden blood loss following OWHTO, proportionate to the size of the correction [40], which could be compounded by chemical thromboprophylaxis. Intravenous tranexamic acid has been shown to reduce blood loss in both tibial [41,42] and femoral osteotomy [43], with reduced length of stay for inpatient surgery.…”
Section: When Planning Osteotomy Patella Height Should Be Taken Into ...mentioning
confidence: 99%